2019
DOI: 10.1186/s12871-019-0680-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk scores for predicting dysphagia in critically ill patients after cardiac surgery

Abstract: BackgroundThis study aimed at developing and validating a scoring model to stratify critically ill patients after cardiac surgery based on risk for dysphagia, a common but often neglected complication.MethodsData were prospectively collected and analyzed from January 2016 to June 2017 from 395 consecutive post cardiac surgery patients at the cardiac care unit (CCU) at a single center; 103 (26.1%) developed dysphagia. Univariate and multivariate logistic analyses were used to identify independent predictors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…This may related to gastric tube is a foreign object that traverses the path way of entire food through invasion of pharynx and esophagus till reached to stomach, that have direct effect on swallowing muscles especially when increase diameters and increase duration of it. This finding is in line with other studies (64,65) which found that the duration of gastric tube is one of the risk factors for certain prognosis value for predicting dysphagia.…”
Section: Discussionsupporting
confidence: 93%
“…This may related to gastric tube is a foreign object that traverses the path way of entire food through invasion of pharynx and esophagus till reached to stomach, that have direct effect on swallowing muscles especially when increase diameters and increase duration of it. This finding is in line with other studies (64,65) which found that the duration of gastric tube is one of the risk factors for certain prognosis value for predicting dysphagia.…”
Section: Discussionsupporting
confidence: 93%
“…The existence of a nasogastric feeding tube can cause mechanical damage to the pharyngeal mucosa, laryngopharyngeal edema, sensory deficits, and swallowing-related muscle atrophy, which decreases swallowing function ( 24 ). Several studies have also reported the risk of feeding tube exposure ( 11 , 25 ). In addition, the long-term existence of the feeding tube can increase the risk of aspiration ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…When using the nomogram, only one variable should be positioned on the corresponding axis, and the points of all variables are summed to determine risk. Some scholars have carried out nomogram research in the field of anesthesia and achieved good results ( Ferrando et al., 2020 ; Ge et al, 2018 ; Hahn, 1995 ; Zhou et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%